Plans for Next-Gen Chips Imperiled. - Santo, B.
In chip industry, a technique called extreme ultraviolet (EUV) photolithography would be ready to start churning out cutting-edge logic chips. Today's technology uses light with a wavelength of 193 nanometers to produce chips with key parts, or features, that measure just 65 nm.
Keywords: EUV technique; Chip industry; Extreme ultraviolet photolithography; Logic chips; Photoresist; Size 65 nm; Wavelength 193 nm